Gene expression of manganese superoxide dismutase in human glioma cells (Faculty of Medicine Universitas Indonesia, 2010)
Aim This study analyze the MnSOD gene expression as endogenous antioxidant in human glioma cells compared with leucocyte cells as control. Methods MnSOD gene expression of 20 glioma patients was analyzed by measuring the relative expression of mRNA and enzyme activity of MnSOD in brain and leucocyte cells. The relative expression of mRNA MnSOD was determined by using quantitative Real Time RT-PCR and the enzyme activity of MnSOD using biochemical kit assay (xantine oxidase inhibition). Statistic analysis for mRNA and enzyme activity of MnSOD was performed using Kruskal Wallis test. Results mRNA of MnSOD in glioma cells of 70% sample was 0.015–0.627 lower, 10% was 1.002-1.059 and 20% was 1.409-6.915 higher than in leucocyte cells. Also the specific activity of MnSOD enzyme in glioma cells of 80% sample showed 0,064-0,506 lower and 20% sample was 1.249-2.718 higher than in leucocyte cells. Conclusion MnSOD gene expression in human glioma cells are significantly lower than its expression in leucocytes cells. (Med J Indones 2010; 19:21-5) Keywords : MnSOD, glioma, gene expression